Registering the Self: The Identity of Women Artists in How to Be Both and A Line Made by Walking - Ferreira, Joicy Silva (Em Tese, 2025)
Women artists have only recently been given the spot of artist protagonists in artist narratives. Their identities are constructed in a constant state of tension, influenced by the myth of the romantic genius, and constantly traversed by gender issues. Thus, this paper studies the construction of women artists’ identities in contemporary artist narratives written by women through a comparative analysis of the novels How to Be Both, by Ali Smith, and A Line Made by Walking, by Sara Baume. It contextualizes these novels’ literary genre, based on the study of artist narratives and their roots in the Künstlerroman tradition, then investigates the identity of women artists and how it is portrayed in the narratives of How to Be Both and A Line Made by Walking.